2019
DOI: 10.1051/matecconf/201929705008
|View full text |Cite
|
Sign up to set email alerts
|

Automation of Operations Design for Complex-Shaped Surfaces Processing

Abstract: Research work is aimed at modeling the process of milling surfaces of complex shape in automated CAD/CAM systems. To reduce labour input of this process, an algorithm for designing milling operations is proposed. The algorithm is implemented in the form of software written in the VBA programming language from Office Excel. The software allows to select cutting tools and cutting modes for roughing, semi-finishing and finishing milling. The initial data for this are: processed material, part configuration, profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Considerable variation of this dependence with theoretical evaluation by M. A. Velikanov made for large particles can be explained by the influence of electrodynamics' effects, which can occur between particles of the fine particulate matter in the aquatic environment, as indicated by B. V. Deryagin, W. J. London. Walker [1,6,8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable variation of this dependence with theoretical evaluation by M. A. Velikanov made for large particles can be explained by the influence of electrodynamics' effects, which can occur between particles of the fine particulate matter in the aquatic environment, as indicated by B. V. Deryagin, W. J. London. Walker [1,6,8].…”
Section: Resultsmentioning
confidence: 99%
“…Researches by B.M. Levin et al [1][2][3][4][5][6][7][8][9][10][11][12][13] showed that for shallow soils, the rate of constrained sedimentation is subject to…”
Section: Methodsmentioning
confidence: 99%
“…CAM-системы позволяют разрабатывать управляющие программы для обработки сложно-профильных поверхностей (СПП). В работе [12] Маркова М.И. описала методику проектирования операций фрезерования СПП, в которой назначение видов обработки ведется исходя из точности и шероховатости обрабатываемой поверхности.…”
unclassified